Women’s empowerment and the will to change: evidence from Nepal - Buisson, Marie-Charlotte; Clement, Floriane; Leder, S. (Elsevier, 2022)
A static and apolitical framing of women’s empowerment has dominated the development sector. In contrast, we assess the pertinence of considering a new variable, the will to change, to reintroduce dynamic and political processes into the way empowerment is framed and measured. This article uses a household survey based on the Women’s Empowerment in Agriculture Index (WEAI) and qualitative data collected in Nepal to analyze how critical consciousness influences women’s will to change the status quo and the role of visible agency, social structures, and individual determinants in those processes. A circular process emerges: women with higher visible agency and higher critical consciousness are more willing to gain agency in some, but not all, of the WEAI empowerment domains. This analysis advances current conceptualizations of empowerment processes: the will to change offers valuable insights into the dynamic, relational and political nature of women’s empowerment. These findings support the design of development programs aiming at increasing visible agency and raising gender critical consciousness and argue for improving the internal validity of women’s empowerment measurement tools.